From farm to click: Understanding consumer motivation for buying agricultural products online - Mohd Norafindy, Siti Nur Athirah; Musa, Marlia; Ahmad, Zulaiha (International Journal of Accounting, Finance and Business, 2026)
In the post-COVID-19 pandemic era, the global surge in internet users has underscored the internet's pivotal role in accelerating digitalisation across various societal domains, significantly altering consumer purchasing behaviours with a pronounced shift towards online-oriented activities, including the agricultural industry. This study aims to identify the factors that motivate consumers to purchase agricultural products via online platforms among UiTM Perlis staff. Convenience sampling has been employed to gather information from a consumer who has experience purchasing agricultural products through online platforms. A set of questionnaires was developed in Google Forms. It has then been distributed via online platforms and direct surveys to the targeted respondents. A total of 159 respondents have returned the questionnaire and have proceeded to data analysis. A multiple regression analysis has been applied to measure the significance of independent variables (availability of information, quality, price and perceived risk) toward the dependent variable (consumers' preferences to purchase agricultural produce and products via online platforms). The findings of the study reveal that the availability of information and price factors show a positive and significant influence on consumers' preferences to purchase agricultural produce and products via online platforms. While the other two factors, namely quality and perceived risk, were insignificantly influencing consumers' preferences to purchase agricultural produce and products via online platforms. Sellers and related agencies such as the Malaysian Communications and Multimedia Commission (MCMC) are encouraged to go beyond these factors, employing diverse strategies to build trust and convince consumers to purchase online